Development of a module for the detection and measurement of greenhouse gases - Cabana Cáceres, Maritza Raquel (2023)
The greenhouse effect produced by the emission of gases generates a lack of protection in the environment that grows more and more annually due to the millions of CO2 emissions in the different environments, for which a greenhouse prototype was built through a set of engineering areas. An automated system for monitoring and detection of methane, CO2 and CO gases with a solar panel, for which the design of the circuit, design of the printed plate and design of the solar panel recharging system, selection of polluting gas sensors was carried out, assembly of the components on the PCB, development of the control and automation program with the ATMEGA328P microcontroller, an adaptation of the cubicle and assembly, tests of sending the data by GPRS to a server in different zones and times of high contamination.